2013
DOI: 10.1128/cvi.00451-13
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous Detection of Antibodies against Apx Toxins ApxI, ApxII, ApxIII, and ApxIV in Pigs with Known and Unknown Actinobacillus pleuropneumoniae Exposure Using a Multiplexing Liquid Array Platform

Abstract: c Surveillance for the presence of Actinobacillus pleuropneumoniae infection in a population plays a central role in controlling the disease. In this study, a 4-plex fluorescent microbead-based immunoassay (FMIA), developed for the simultaneous detection of IgG antibodies to repeat-in-toxin (RTX) toxins (ApxI, ApxII, ApxIII, and ApxIV) of A. pleuropneumoniae, was evaluated using (i) blood serum samples from pigs experimentally infected with each of the 15 known A. pleuropneumoniae serovars or with Actinobacill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
12
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 47 publications
(71 reference statements)
1
12
0
2
Order By: Relevance
“…Apx exotoxins secreted by Actinobacillus pleuropneumoniae are toxic factors that deeply impact the pathogenesis of porcine pleuropneumonia. Former studies reported that ApxIVA is produced by all the 15 serotypes of APP and is highly specific to APP (Wei et al, 2012;Giménez-Lirola et al, 2014). Due to the specificity of the ApxIVA gene to the Actinobacillus pleuropneumoniae strains, the detection assays based on this gene have been widely explored for the identification of the Actinobacillus pleuropneumoniae strains (Schaller et al, 2001;Dreyfus et al, 2004;Turni and Blackall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Apx exotoxins secreted by Actinobacillus pleuropneumoniae are toxic factors that deeply impact the pathogenesis of porcine pleuropneumonia. Former studies reported that ApxIVA is produced by all the 15 serotypes of APP and is highly specific to APP (Wei et al, 2012;Giménez-Lirola et al, 2014). Due to the specificity of the ApxIVA gene to the Actinobacillus pleuropneumoniae strains, the detection assays based on this gene have been widely explored for the identification of the Actinobacillus pleuropneumoniae strains (Schaller et al, 2001;Dreyfus et al, 2004;Turni and Blackall, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of multiple isolates of H. parasuis, particularly in URT samples (27)(28)(29), is one of the major challenges in designing a prospective molecular tool for determining virulence. Current surveillance methods for other pathogens such as Actinobacillus pleuropneumoniae operate on an individual isolate level, where the detection of the bacterium initiates a more thorough investigation at the single-colony level to look for the presence of toxins (30,31). We see this pathotyping mPCR as a useful tool for surveillance as a preventative measure.…”
Section: Discussionmentioning
confidence: 99%
“…O contágio geralmente ocorre após inalação de aerossóis ou contato direto, o microrganismo inalado coloniza o tecido pulmonar aderindo-se ao muco, proteínas e a células hospedeiras com posterior multiplicação no local (Chiers et al 2010). O monitoramento do status da doença em rebanhos, o controle e a erradicação são de fundamental importância devido a características de contágio rápido deste agente, para impedir que animais portadores sejam introduzidos em rebanhos saudáveis (Tremblay et al 2013).Testes indiretos são muito utilizados (Machado et al 2001, Shin et al 2011, Eamens et al 2012a,b, GimenezLirola et al 2014,para detecção simultânea de anticorpos para toxinas com sensibilidade de 82,7% e especificidade de 100% (Gimenez-Lirola et al 2014). São descritos testes de ELISA monovalentes e polivalentes para sorotipos, com sensibilidade e especificidade variando de 88,3% a 96,6% (Machado et al 2001).…”
unclassified
“…Testes indiretos são muito utilizados (Machado et al 2001, Shin et al 2011, Eamens et al 2012a,b, GimenezLirola et al 2014,para detecção simultânea de anticorpos para toxinas com sensibilidade de 82,7% e especificidade de 100% (Gimenez-Lirola et al 2014). São descritos testes de ELISA monovalentes e polivalentes para sorotipos, com sensibilidade e especificidade variando de 88,3% a 96,6% (Machado et al 2001).…”
unclassified